A Study of Taboo Words among Students in the Classroom Interaction - Yenni Hasnah; Adib Jasni Kharisma; Lira Fibay (English Teaching and Linguistics Journal (ETLiJ), 2022)
This research deals with the use of taboo words among students in the classroom interaction. It was intended to investigate the types and functions of using taboo words when the students communicated each other in the class. The method used in this study was qualitative research. The data were obtained from the observed and recorded learning activities in the classroom by focusing on the utterances of taboo words used among students. The data collected were analyzed qualitatively including data collection, data condensation, data display, and drawing conclusion. The findings show that three types of taboo words were realized on the students interaction, namely: vulgarity, epithets, and profanity. Meanwhile another type of taboo word (obscenity) was not existed. Then, it was also revealed that there were three functions indicated by students in applying taboo words when they were communicating each other; to draw attention to one self, to show contempt, and to be provocation. In conclusion, not all taboo words categories were realized in the students classroom interaction.